Families of Models that Cross Levels of Resolution: Issues for Design, Calibration and Management - Davis, P.K.; Hillestad, R. (WSC, '93: Winter Simulation Conference Proceedings, 1993)
This review paper summarizes an ARPA-sponsored project to study variable-resolution modeling (VRM) and the connection of models across levels of resolution. We describe work introducing basic concepts, highlighting a design approach called integrated hierarchical variable-resolution modeling (IHVR), exploring mathematically some long-standing issues of aggregation in ground-combat modeling, and experimenting with cross-organizational efforts to develop and compare models created with different techniques and perspectives. We also describe highlights of a conference held in May, 1992 and touch briefly on some subsequent work. Despite the substantial progress, we conclude that the VRM problem is central, difficult, and greatly under invested. It should be approached as a matter of military science rather than technology, although we discuss new software tools that can be quite valuable.